Structure of hard-bottom communities in boulder fields of the SW Baltic Sea - Franz, Markus; von Rönn, Gitta Ann; Barboza, Francisco Rafael; Karez, Rolf; Reimers, Hans-Christian; Schwarzer, Klaus; Wahl, Martin (PANGAEA, 2019)
Three study regions along the shallow waters of the southwestern Baltic Sea coastline were selected for a sampling of hard-bottom communities. Within each study region, three boulder fields (=sampling stations) were chosen. At each sampling station, samples were taken by SCUBA divers at 5 m water depth by scraping off the attached biota within a 10 x 10 cm sampling frame. In addition, the length, width and height of each sampled boulder were measured. As a result of the used sampling frame, the smallest boulder that was sampled had a diameter of ≈ 15 cm. In case the diameter of a boulder exceeded 30 cm, sampling was repeated along the longest axis of the boulder with 30 cm separating neighboring sampling frames. The collected material was fixed in a buffered formaldehyde solution (final concentration of 4%) and identified to the lowest taxonomic level possible. Accordingly, the species richness and the presence/absence of benthic species was recorded for each boulder. Since larger boulders contained several samples, species lists for areas of single frames were cumulated to obtain the total species inventory of the respective boulder. In addition, the functional diversity of the communities is given. All recorded species were categorized based on adult body size, growth form, trophic type and motility (see related article for further information). Consequently, each species was assigned to a functional group (four letters code) by the combination of its functional traits.
Keywords: Baltic Sea; Benthos; Biodiversity; boulder field; environmental filtering; hard-bottom communities